The complexity, function and applications of RNA in circulation - Etheridge, Alton; Gomes, Clarissa P.; Pereira, Rinaldo W.; Galas, David; Wang, Kai (Frontiers in Genetics, 2013)
Blood carries a wide array of biomolecules, including nutrients, hormones and molecules that are secreted by cells for specific biological functions. The recent finding of stable RNA of both endogenous and exogenous origin in the circulation raises a number of questions and opens a broad, new field: exploring the origins, functions and applications of these extracellular RNA molecules. These findings raise many important questions, including: what are the mechanisms of export and cellular uptake, what is the nature and source of their stability, what molecules do they interact with in the blood, and what are the possible biological functions of the circulating RNA. This review summarizes some key recent developments in circulating RNA research and discusses some of the open questions in the field.